A TEXT BOOK OF MYCOLOGY - HAIT, GPINATH (London New Central Book Agency, 2016)
About the Book: A Textbook Of Mycology Set in the mould of the classifications furnished in Ainsworth and Bisbys "Dictonary of the Fungi" (10th edition, 2008), this text is ideally meant for the undergraduate and postgraduate students of Botany of all leading Indian universities. Based on morphology, ultra-structure, biochemistry and molecular biology, the book imparts a fresh insight into the exciting world of fungi and other fungus-like organisms.
Keywords: Botany; Mycology